2017
DOI: 10.1177/2050640616662160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pull and introducer percutaneous endoscopic gastrostomy techniques in patients with head and neck cancer

Abstract: The push and introducer PEG techniques seem to be both safe and effective but present different complication profiles. The choice of PEG technique in patients with HNC should be made individually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
(112 reference statements)
3
12
1
2
Order By: Relevance
“…PEG placement is done by puncturing the abdominal wall; therefore, bleeding is a logical consequence and may be underreported by physicians. Periprocedural minor bleeding is reported significant more with the push‐type, which is supported by two other studies 20,21 . Minor bleeding is defined as no intervention was required, whereas major bleeding surgical or endoscopic intervention was needed.…”
Section: Discussionsupporting
confidence: 55%
“…PEG placement is done by puncturing the abdominal wall; therefore, bleeding is a logical consequence and may be underreported by physicians. Periprocedural minor bleeding is reported significant more with the push‐type, which is supported by two other studies 20,21 . Minor bleeding is defined as no intervention was required, whereas major bleeding surgical or endoscopic intervention was needed.…”
Section: Discussionsupporting
confidence: 55%
“…Evidências sugerem que o método de escolha para realização de gastrostomia em paciente com CCP deve buscar evitar o contato entre a sonda e o tecido tumoral, uma vez que a passagem da sonda pode translocar células tumorais e implantá-las na mucosa gástrica. ( 2 ) A técnica de escolha para realização da GEP deve ser feita individualmente, considerando caso a caso, ( 7 ) no entanto a técnica de tração é preferida quando não há obstrução do trato gastrintestinal superior, dada a menor taxa de eventos adversos a curto prazo. ( 6 ) Outras opções podem ser consideradas, como a técnica percutânea com fluoroscópio, uma vez que não necessita de sonda e nem da passagem desta pelo sítio tumoral; ( 2 ) a realização de laparoscopia ou procedimento aberto para posicionamento da sonda (com os devidos cuidados para manter o sítio cirúrgico e o equipamento separados, buscando evitar contaminação da mucosa gástrica, que possa posteriormente gerar novas metástases); ou até mesmo considerar a quimioterapia ou quimioradioterapia antes da GEP em paciente com intenção de cura.…”
Section: Discussionunclassified
“…Evidence suggests that the method of choice for gastrostomy in patient with HNC should seek to avoid contact between the probe and the tumor tissue, since the passage of the probe can translocate tumor cells and implant them in the gastric mucosa. (2) The technique to perform EPG should be individually chosen, considering case-by-case; (7) however, the traction technique is preferred when there is no obstruction in the upper gastrointestinal tract, given the lower rate of short-term adverse events. (6) Other options may be considered, such as the percutaneous technique with fluoroscope, since there is no need for a probe or its passage through the tumor site; (2) performance of laparoscopy or open procedure (with the due care to maintain separate the surgical site and the equipment, in order to avoid contamination of the gastric mucosa, which might posteriorly generate new metastases); or even to consider chemotherapy or chemotherapy plus radiation therapy before EPG in an patient with the purpose of curing.…”
Section: ❚ Introductionmentioning
confidence: 99%
“…Thus, the use of a direct gastric puncture technique for percutaneous feeding tube placement in patients with proximal GI cancer has been recommended by several authors, especially in patients receiving radical therapy with curative intent [20,25]. Comparative studies have shown similar complication rates, except for a more common occurrence of delayed tube disfunction and minor bleeding episodes with the introducer approach [30,31].…”
Section: Nasal Tubesmentioning
confidence: 99%